Cyclin-dependent kinase inhibitors, roscovitine and purvalanol, induce apoptosis and autophagy related to unfolded protein response in HeLa cervical cancer cells - Sarıkaya, Bahar; Çoker Gürkan, Ajda; Temizci, Benan; Palavan Ünsal, Zeynep Narçın; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN; KILBAŞ, PELİN ÖZFİLİZ (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2018)
Roscovitine (Rosc) and purvalanol (Pur) are competitive inhibitors of cyclin-dependent kinases (CDKs) by targeting their ATP-binding pockets. Both drugs are shown to be effective to decrease cell viability and dysregulate the ratio of pro- and anti-apoptotic Bcl-2 family members, which finally led to apoptotic cell death in different cancer cell lines in vitro. It was well established that Bcl-2 family members have distinct roles in the regulation of other cellular processes such as endoplasmic reticulum (ER) stress. The induction of ER stress has been shown to play critical role in cell death/survival decision via autophagy or apoptosis. In this study, our aim was to investigate the molecular targets of CDK inhibitors on ER stress mechanism related to distinct cell death types in time-dependent manner in HeLa cervical cancer cells. Our results showed that Rosc and Pur decreased the cell viability, cell growth and colony formation, induced ER stress-mediated autophagy or apoptosis in time-dependent manner. Thus, we conclude that exposure of cells to CDK inhibitors induces unfolded protein response and ER stress leading to autophagy and apoptosis processes in HeLa cervical cancer cells.
Keywords: Roscovitine; Purvalanol; Cervical cancer; ER stress; Autophagy; Apoptosis; ENDOPLASMIC-RETICULUM STRESS; POLYAMINE CATABOLIC PATHWAY; FINE-TUNING MOLECULE; MEDIATED APOPTOSIS; CDK-INHIBITOR; ER STRESS; IN-VITRO; ACTIVATION; CROSSTALK; MECHANISMS